The Effect of Kahoot-Based Interactive Learning on Students' Learning Outcomes in Qur'an-Hadith Education - Qurrota A'yun; Imam Mashuri; Rifqi Firdaus; Kholilur Rahman (Journal of Educational Management Research, 2026)
This study aimed to examine the effect of Kahoot-based interactive learning on students' learning outcomes in Qur'an-Hadith Education. A quantitative approach was employed using a One-Group Pretest–Posttest Design to evaluate changes in students' cognitive achievement before and after the implementation of Kahoot-based learning. The study involved 33 students, and data were collected through pretest and posttest assessments. Prior to hypothesis testing, the research instrument was confirmed to be reliable, with a Cronbach's Alpha coefficient of 0.826. The collected data were analyzed using normality, homogeneity, and paired-sample t-tests. The findings indicated that the data were normally distributed (p = 0.200 > 0.05) and homogeneous (p = 0.599 > 0.05). Furthermore, the paired-sample t-test revealed a statistically significant difference between the pretest and posttest scores (p < 0.001). Students' mean scores increased from 77.79 on the pretest to 85.30 on the posttest, demonstrating a significant improvement in learning outcomes following the intervention. These findings suggest that Kahoot-based interactive learning is an effective instructional strategy for enhancing students' cognitive achievement while fostering more engaging and student-centered learning experiences in Qur'an-Hadith Education. The study provides practical implications for integrating game-based digital learning into Islamic Religious Education to support more effective classroom instruction.